INTEGRATIVE CONCEPTUAL ANALYSIS AS A BASIS FOR THE FORMATION OF GOGNITIVE MAP OF A LEXICAL UNIT - N. I. Shapilova (Вестник Кемеровского государственного университета, 2015)
The subject of study in this paper is a conceptual analysis of lexical units in language and communicative-pragmatic aspects. The purpose of the study is to give a theoretical justification and to show the possibilities and achievements of integrative research in the context of modern cognitive direction. Integrative approach to the semantics of linguistic units stems from a tendency to generalize, both in theory and in practical analysis, which is largely due to the inclusion in the modern anthropocentric paradigm of research in the cognitive and functional-communicative orientation. The article examines the conceptual line of research of ontological and epistemological orientation, which allows one to represent the formation of integrative semantics of lexical units. In the process of identifying ontological semantics, the author discusses the formation of the concept at the stage of concrete-sensory perception, comprehension and verbalization in the process rehabilitating of human activity. The second line is based on the variety of conceptual semantics and accordingly various sources of its identification: lexicographic, associative, and textual ones. Such an integrated multidimensional analysis is performed on the examples of emotional vocabulary, initially rooted in antiquity and containing a religious component to the semantics, subsequently mostly lost due to the disappearance of religion, which leads to the desacralization of the semantics of the vocabulary in question. Recent researches turn to the development of cognitive modeling, thus aiming the field of conceptual analysis at the creation of cognitive maps of lexemes.